Eje de Tratamiento Laboral con Relación a la Rehabilitación Penitenciaria en Ecuador - Erazo Pauta, Jorge Luis (2024)
The Labor Treatment Axis in Relation to Prison Rehabilitation in Ecuador investigates the importance of prison labor in the rehabilitation of persons deprived of liberty. It highlights the constitutional and normative framework that supports the labor treatment axis as a crucial tool for the rehabilitation and social reintegration of inmates in the Ecuadorian penitentiary system. The main objective of the study is to evaluate the effectiveness of the labor treatment axis in prison rehabilitation and to analyze its impact on the reduction of criminal recidivism. A mixed methodology was used, including empirical, descriptive, deductive, analytical, maieutic and statistical methods. The techniques used were surveys and interviews with a sample of 25 people, including 20 3 inmates and 5 prison guides. The results show that 75% of the inmates surveyed are aware of the labor treatment axis, which indicates a good dissemination and understanding of the program. In addition, it was found that participation in work activities within the prisons helps to develop work, social and emotional skills, promoting the autonomy and dignity of the inmates. In conclusion, the study highlights that the labor treatment axis is an effective tool for prison rehabilitation, promoting social reintegration and reducing criminal recidivism. It is recommended that these programs be strengthened and their implementation improved to maximize their benefits for both inmates and society in general.